Life Cycle of Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae) on Potato in Laboratory Condition in Nepal - Bhat, Binu; Bajracharya, Ajaya Shree Ratna (Journal of the Plant Protection Society, 2024)
Pea leafminer, Liriomyza huidobrensis, is a key pest of potato in mid hills of Nepal causing up to 90% foliar damage. The confirmation of the insect and determination of its life cycle is the basic requirement for development of integrated pest management protocol technology. Considering the fact, life cycle of L. huidobrensis was studied at 27 ± 2 °C temperature and 70 ± 5% relative humidity at the National Entomology Research Center, Lalitpur, Nepal on potato cv. Khumal Seto from March to April, 2023. The insect species was confirmed as L. huidobrensis on the basis of morphological similarities of bristles, male genitalia and wing venation with the reference species L. huidobrensis. The average duration of pre-oviposition, egg, larval and pupal periods were 2.35, 3.18, 4.47 and 7.88 days, respectively. Adult male and female longevity was 3 days without feeding and 6 and 10 days with honey water feeding for both male and female. The male and female adult emergence ratio was 1:1.41. Eggs were oval and white in colour measuring 0.30 mm long and 0.10 mm. Pupae were coarctate type measuring 2.10 mm in length and 0.90 mm in breadth. Wing span of adult female and male were 1.92 mm and 1.70 mm in length, while width measured 0.78 mm and 0.67 mm, respectively.